A Study on the Synthesis, Characterization, and Biological Efficacy of Certain Copolyesters Containing Chalcone Moiety in the Main Chain - Rais, Mohd Imran (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: To synthesise random copolyesters containing chalcone moiety in the main chain, their characterization and biological activity. Material and Methods: A series of eight random copolyesters were synthesized by the polycondensation of a chalcone diol with two aromatic diacid chlorides and four aliphatic diacid chlorides. The two aromatic diacid chlorides used were terephthaloyl chloride and isophthaloyl chloride. The aliphatic diacid chlorides used were adipoyl chloride, oxalyl chloride, glutaryl chloride, and succinyl chloride. The chalcone diol was synthesized by acid catalyzed Claisen-Schmidt reaction. Results and Discussions: These copolyesters were characterized by qualitative solubility tests and viscosity measurements. The microstructure of the repeating units available in the copolyester main chain was established by Fourier transform infrared, 1H-nuclear magnetic resonance (NMR), and 13C-NMR spectroscopic techniques. DSC was apply to study thermal analysis. The well diffusion method was employed to establish the biological efficacy of these eight copolyesters by involving Gram-positive and Gram-negative bacteria. Conclusion: The presented work reports random copolyester preparation by polycondensation method and viscosity measurements tells about that the prepared compounds are of high molecular weight. others like FTIR, NMR, Solubility measurements and DSC characterize them. Biological properties was also studied.